Asymmetric Synthesis of 3-Alkyl 3-Alkyloxy-2-oxindoles by Enantioconvergent Alkoxylation with Alcohols - Song, Yilun; Liu, Deyang; Dong, Shunxi; Feng, Xiaoming (Synthesis, 2025)
A highly enantioselective alkoxylation reaction of 3-bromo-3-substituted 2-oxindoles with alcohols was achieved by a chiral Ni(II)/N,N′-dioxide complex. This strategy provided an efficient route to various enantioenriched 3-alkyl 3-alkyloxy-2-oxindoles with good yield and enantiomeric ratio (40 examples, up to 99% yield, 95:5 er). Moreover, phenol and benzenethiol were also compatible with the reaction conditions. The gram-scale synthesis of an optically active product and its further transformation into CPC-1 analogue demonstrated the potential utility of the method. In addition, a catalytic cycle as well as a possible working mode was provided to understand the enantioselectivity of the reaction.
Keywords: asymmetric synthesis; alkoxylation; 3-substituted oxindoles; chiral N,N′-dioxide; nickel